HUBUNGAN PERSEPSI KEARIFAN LOKAL DENGAN SIKAP KONSERVASI MASYARAKAT DESA LENCOH KECAMATAN SELO DI TAMAN NASIONAL GUNUNG MERAPI - Ernawati Ernawati; Eka Putri Azrai; Sri Supardi Wibowo (Universitas Negeri Jakarta, 2016)
Local wisdom refers to ideas and local knowledge which are wise, full of wisdom, good and virtuous beliefs that made, owned, also carried out by local people in that area. People of Lencoh village are applying local wisdom filled with Javanese culture in order to interact with the environment and use natural resources. This study aims to determine the correlation between perception of local wisdom and conservation attitude of Lencoh village people in Mount Merapi National Park. The study was conducted in Lencoh village, Selo sub-district in January 2016. The method used is the descriptive methods with correlational study. There are 95 respondents from the three hamlets. The data is using questionnaires and interviews. The results showed 56,84% and 43,16% of respondents have a enough and high local wisdom perception, and 8,42% and 91,58% of respondents have a enough and good conservation attitude. Hypothesis is tested using simple linear regression analysis, obtained Y = 47.262 + 0.703X and Pearson Product Moment Correlation test at Î± = 0.01, obtained rxy = 0.678 indicates a strong correlation between local wisdom perception and conservation attitude of a Lencoh village people. The results of this research prove there is a positive correlation between local wisdom perception and conservation attitude of Lencoh village people on Mount Merapi National Park.